A meta-analysis of randomized controlled trials of a traditional Chinese medicine prescription, modified RunChang-Tang, in treating functional constipation. Issue 20 (21st May 2021) - Zhao, Xiankun; Fang, Yuxiao; Ye, Jing; Qin, Feng; Lu, Wenzhu; Gong, Hanlin
Abstract: Background: Modified Runchang-Tang (MRCT), a Chinese herbal medicine, is widely used to treat functional constipation (FC), which is a common digestive system disease. However, its efficacy has not been evaluated systematically and objectively. Thus, a meta-analysis was conducted to assess the efficacy and safety of MRCT for treating functional constipation. Methods: We searched for relevant publications from Embase, Medline, The Cochrane Library, Chinese Biomedical Literature Database, China National Knowledge Infrastructure, Chinese Scientific Journals Database, and Wanfang Data for relevant literature. The timeframe of retrieval was set from the founding date of each database to July 15, 2020. Result: A total of 26 randomized controlled trials with 2103 individuals were included in this meta-analysis. All trials were conducted in mainland China and were written in Chinese. The results showed that MRCT monotherapy provided better symptom relief in FC patients compared to prokinetic agent monotherapy (odds ratio, [OR] = 4.06), osmotic laxatives (OR = 4.39) and stimulant laxatives (OR = 2.99). Additionally, there were no obvious adverse effects in MRCT group compared with control group. Conclusion: MRCT treatment is an efficient and safe treatment for FC. However, considering the limitations of this study, further well-designed randomized controlled trials are required to validate this conclusion.